Evaluasi Bantuan Langsung Tunai Pemerintah dan Nonpemerintah Terhadap Pengeluaran Masyarakat (Evaluation of Government and Non-Government Cash Assistance on Expenditure) - Meilianna, Ruth (Jurnal Ekonomi & Kebijakan Publik, 2024)
The direct cash transfer (BLT) program is still one of the assistance programs maintained to reduce poverty and to increase welfare in Indonesia. Cash transfers are considered to be able to protect people's purchasing power and consumption due to various pressures such as price increases, where purchasing power and consumption can reflect welfare. Despite the pros and cons, this type of assistance is still maintained because it has its own advantages. A number of researchers have analyzed the effectiveness of cash transfer programs, but unfortunately they are limited to government cash transfer programs and limited to non-government cash transfer programs, so there is a need for research that examines the effectiveness of both government and non-government cash transfer programs with household data and comparisons between the two. This study aims to analyze the effectiveness of government and non-government cash transfer programs and measure whether they are effective in improving welfare, which in this case means increasing non-food expenditures of beneficiaries. This study uses the propensity score matching method and data from the 2014 Indonesian Family Life Survey (IFLS). The results show that both programs affect the increase in non-food expenditure, but the government-run BLT program increases non-food expenditure at a higher rate.AbstrakProgram bantuan langsung tunai (BLT) masih menjadi salah satu program bantuan yang dipertahankan untuk mengurangi kemiskinan dan meningkatkan kesejahteraan di Indonesia. BLT dianggap dapat melindungi daya beli masyarakat dan konsumsi akibat berbagai macam tekanan seperti kenaikan harga, di mana daya beli dan konsumsi dapat menggambarkan kesejahteraan. Meskipun terdapat pro dan kontra, jenis bantuan ini tetap dipertahankan sebab memiliki kelebihan tersendiri. Sejumlah peneliti telah menganalisis efektivitas dari program BLT, sayangnya hanya terbatas pada program BLT yang berasal dari pemerintah saja, dan terbatas bagi yang nonpemerintah sehingga dibutuhkan penelitian yang membahas efektivitas bantuan dari pemerintah maupun dari nonpemerintah dengan data rumah tangga dan perbandingan di antara keduanya. Penelitian ini bertujuan menganalisis efektifitas program BLT dari pemerintah maupun nonpemerintah dan mengukur apakah keduanya efektif dalam meningkatkan kesejahteraan, yang dalam hal ini meningkatkan pengeluaran nonmakanan penerima bantuan. Penelitian ini menggunakan metode propensity score matching dan menggunakan data Indonesian Family Life Survey (IFLS) 2014. Hasil menunjukkan bahwa keduanya memengaruhi peningkatan pengeluaran nonmakanan, namun BLT yang dijalankan oleh pemerintah meningkatkan pengeluaran nonmakanan lebih tinggi.